Sistem Prediksi Rata-Rata Pemakaian Bahan Bakar Minyak Berbasis Web Menggunakan Algoritma Naive Bayes (Studi Kasus : PT. Hijrah Insan Karima) - Tugianto .; Onki Alexander; Risma Ekawati (Jurnal ICT : Information Communication & Technology, 2021)
Companies must be able to take advantage of their assets for the progress of the company without anything that harms or hinders the progress of the company. Then began to develop a system that can help companies monitor their resources, in this case assets owned in the form of vehicles and human resources, the system is a group of elements that are integrated with the same intent to achieve a goal. Then made a web-based prediction system that applies the Naive Bayes Algorithm in predicting the average fuel consumption of PT. The Migration of the Karima People. In the process used methods consisting of observation, interviews, literature study to find the required data, data testing and system development using the Waterfall method. In this way, it will be easier to monitor, analyze and determine strategies that will be implemented in the future based on the existing track record. The average standard value for the criteria for the type of car and fuel has been found to be in a ratio of 1:7 double cars, 1:8 ankle cars, (1:11,1:10,1:9) small cars. With a web-based system and the Naive Bayes Algorithm, it will make it easier to monitor the fuel consumption of each operated fleet